Effect of anti-oxidants and oxidative stress parameters on ram semen after the freeze-thawing process (vol 75, pg 128, 2007) - Bucak, Mustafa Numan; Atessahin, Ahmet; Yuce, Abdurrauf (Elsevier, 2008)
[Abstract Not Available]